(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Backgrounds and Objective: Osteoarthritis (OA) is a set of joint disorders caused by different factors but has the same pathological changes. OA of the knee joint occurs mainly due to the tibiofemoral and patelofemoral joints as a continuous body weight support throughout human life both static and dynamic, thus gradually causing changes in the structure of the knee joint tissue. This study aimed to know the function and strengthening of muscle strength of quadriceps and hamstring in patient with knee osteoarthritis. Method: Twenty-two patients with knee OA (average age of 51.7 years; range 40 to 65 years) were randomly grouped into intervention group (agility and perturbation exercises plus strengthening exercise of quadriceps and hamstring muscles) and the control group (strengthening exercise of quadriceps and hamstring muscles). Both group participated in a four-week exercise. Balance function, quadriceps and hamstring muscles strength (BBS, TUG, EN-Tree 1 RM) were assessed before and after intervention. Result: The intervention and control group improved 1 RM quadriceps muscle (p = 0.0001) and 1 RM hamstring muscle (p = 0.0001) but there was no statistically significant difference between groups, score of BBS in intervention group improved significantly (p = 0.0001) and statistically increased significant between groups (p = 0.0001), score of TUG in intervention group improved significantly (p = 0.002) but there was no statistically significant difference between groups (p = 0.324). Conclusion: Supplementation of agility and perturbation exercises on strengthening exercise of quadriceps and hamstring to balance function provided additional benefit with respect to the BBS score after four-week intervention of patients with knee osteoarthritis.